Is Man a Being with Deficiencies? Hans-Eduard Hengstenberg’s Polemic with Arnold Gehlen - Kożuchowski, Józef (Sensus Historiae, 2021)
The paper consists of two parts, the first of which is an introduction to the second, more fundamental, containing a polemic between Hans-Eduard Hengstenberg and Arnold Gehlen. This text allows us to learn about Hengstenberg’s arguments developed from phenomenological and metaphysical positions. It challenges the thesis of the German anthropobiologist, according to which man, unlike other higher mammals, is a defective being in terms of biological constitution, because he is defined mainly by deficits. The introduction attempts to show the specificity of Hengstenberg’s philosophizing (integration of phenomenology and metaphysics) and the notion of matter-of-factness, underlying both its foundations and the text of the polemic with Gehlen, together with its ontological source (human spirit). In addition, the context in which this polemic has its source and cause has been defined.